Risk of impacts from extreme weather and climate in river-based tilapia cage culture in Northern Thailand - Phimphakan Lebel (2018)
Copyright © 2015 Inderscience Enterprises Ltd. This paper analyses the direct impacts of extreme weather, high and low flow events, seasonality and other climate-related phenomena on river-based tilapia cage aquaculture in Northern Thailand. An interdisciplinary approach was taken, which included analysis of secondary water flow and meteorological data, quantitative and qualitative surveys of farmers' experiences with extreme events, and direct observations during critical periods. Findings show that extreme high and low flows adversely impact a substantial fraction of farms, causing damage to cages, fish deaths, slow growth and disease problems. Economic losses are significant and result in financial debt. Compensation and assistance following floods is modest relative to losses, and coverage is incomplete. Probability of extreme flows and impacts vary among locations, are highly seasonal, and vary inter-Annually. These findings are important to improving management of climate-related risks, under both current and future climatic conditions.